1976
DOI: 10.3758/bf03335122
|View full text |Cite
|
Sign up to set email alerts
|

Extended training and multiple shifts: Percentage of reward

Abstract: This is one paper of a series investigating the effects of extended training and multiple succesSve reward shifts. Four groups were run in a straight alley. The control groups received either 75% or 25% reinforcement throughout training. Each experimental group was given 40 acquisition trials at either 75% or 25% reinforcement followed by three shifts of 24 trials each. All groups were given 24 extinction trials. There were initial significant differences betMen the 75% and 25% groups. These differences disapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2

Year Published

1979
1979
1983
1983

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
2
8
2
Order By: Relevance
“…The failure to obtain contrast effects in the nondelay condition is consistent with sucrose studies in which initial shifts in magnitude of reward did not result in a PCE (Shanab et al, 1976) or a NCE (Flaherty et al, 1973;Shanab et al, 1976). Although a NCE is usually readily obtained in food studies under nondelay conditions (Dunham , 1968), some studies have reported negative results for NCE (Weinstock, 1971), as well as for PCE (McCain, Lobb, & Newberry, 1976).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The failure to obtain contrast effects in the nondelay condition is consistent with sucrose studies in which initial shifts in magnitude of reward did not result in a PCE (Shanab et al, 1976) or a NCE (Flaherty et al, 1973;Shanab et al, 1976). Although a NCE is usually readily obtained in food studies under nondelay conditions (Dunham , 1968), some studies have reported negative results for NCE (Weinstock, 1971), as well as for PCE (McCain, Lobb, & Newberry, 1976).…”
Section: Discussionsupporting
confidence: 60%
“…The failure to obtain a NCE in the delay condition and the absence of a PCE or NCE in the nondelay condition are obviously inconsistent with this prediction. The present results receive support from other studies in which a second shift in magnitude of food reward produced neither a significant PCEnor a significant NCE (McCain,Lobb, & Newberry, 1976 ;Weinstock, 1971). These findings , however, are to be contrasted with those of other studies that obtained contrast effects during a second shift with both food reward (Benefield et al, 1974) and sucrose reward (Shanab et al, 1976).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The superiority of the larger percentage in preshift is similar to the McCain et al (1976) finding that 75% reward generated faster responding than 25% reward, at least early in training. Although it is not possible to determine, either from the present data or from the McCain et al results, whether differential percentage would result in differential asymptotic performance, these data do indicate that percentage will influence rate of approach to asymptote.…”
Section: Resultssupporting
confidence: 72%
“…The literature concerning the effects of upshifts in percentage is somewhat ambiguous. While Leung and Jensen (1968) observed positive contrast following upshifts in percentage, several authors have failed to observe such effects (e.g., Lehr, 1974, when magnitude was held constant; McCain, Lobb, & Newberry, 1976;Roop & Nation, 1976). Thus, the present experiment compared a group that received an upshift in reward percentage (from 33% to 100%) to a group that received the higher percentage throughout training.…”
Section: Methodsmentioning
confidence: 95%